Предмет: Алгебра,
автор: morbid20
(x+1)*(x-1)=(x+2)^2 решите задание
Ответы
Автор ответа:
0
Ответ:
x=-1,25
Объяснение:
(x+1)(x-1)=(x+2)^2
x^2-x+x-1=(x+2)(x+2)
x^2-1=x^2+2x+2x+4
x^2-1=x^2+4x+4
x^2-1-x^2-4x-4=0
-4x-5=0
4x=-5
x=-1,25
Автор ответа:
0
(x+1)(x-1)=(x+2)²
x²-1=x²+4x+4
x²-x²-4x=4+1
-4x=5
x=5:(-4)
x=-1,25
Ответ:x=-1,25
Похожие вопросы
Предмет: Другие предметы,
автор: Chocolate52626
Предмет: Литература,
автор: karpenkoia08
Предмет: Математика,
автор: anilorak2
Предмет: Физика,
автор: sadadel